Automatic License Plate Recognition: State of the Art and The Opportunities for Implementation in Indonesia (Literature Review) - Aris Budianto (Journal of Telematics and Informatics, 2018)
The Automatic License Plate Recognition (ALPR) has been becoming a new trend in transportation systems automation. The extraction of vehicle’s license plate information from image or sequence of images can be done without human intervention. Despite such technology has been widely adopted in developed countries, developing countries remain a far-cry from implementing the sophisticated image and video recognition for some reasons. This paper assesses the possibilities of implementing Automatic License Plate Recognition within Indonesia’s circumstances. Previous knowledge suggested in the literature, and state of the art of the automatic recognition technology is amassed for consideration in future research and practice.